Motiv siamskih dvojčkov in motivno-tematska tradicija Doppelgängerja - Virk, Tomo (Primerjalna književnost, 2011)
This paper discusses the motif of the Siamese twins in modern artistic production primarily based on Lojze Kovačič's "Zgodba o dvoglavem sinu" (The Story of the Two-Headed Son). Relying on psychoanalytic interpretation, it shows that the motif is placed within the tradition of the romantic Doppelgänger and also analyzes the modifications this motif tradition has undergone in the present.
Keywords: Kovačič, Lojze, 1928-2004; Slovene literature; slovenska književnost; literarni motivi; dvojniki; Doppelgänger; psihoanaliza